Pembuatan Area Pembibitan Mangrove Desa Pangkahkulon-Gresik - Defri Yona; Dhira Kurniawan; Ledhyane Ika Harlyan; Adrian Sakti Gangsar Pinilih; Siti Nur Khabibah; Yanida Azhari Julianinda (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Pangkahkulon Village is designated as the Ujungpangkah Mangrove Essential Ecosystem Area (KEE MUP) because the mangrove forest area in this area is a migration route and habitat for pelicans from Australia and is designated as a Ramsar site. Awareness to maintain the mangrove ecosystem is carried out by rehabilitating mangroves by the community supervisory group (POKMASWAS) Pangkahkulon. However, Pangkahkulon Village does not have a mangrove nursery area that is easily accessible yet, it takes approximately 40 minutes by boat to get to the nursery area which is located at the estuary of the Bengawan Solo River. Based on the results of discussions with Pangkahkulon Village officials, the right mangrove nursery area is in the village port area which is a strategic area for various community activities. This Community Service (PKM) activity will produce a mangrove nursery area according to its designation, training on nursery mechanisms from mangrove nursery experts as well as learning media for mangrove ecosystem functions. In addition, the output of this activity can help the village government plan to open a mangrove edupark in Pangkahkulon Village.